Multiple resistance of Conyza sumatrensis to Chlorimuronethyl and to Glyphosate - Santos,G. (2014)
Weed resistance to herbicides has been a major issue in Brazil, mainly due to the inefficiency of the herbicides used in no-till areas and to the high cost of these herbicide treatments. Failures in controlling the weed Conyza have been reported in Western and Northern grain crop areas in Paraná (Brazil). This work aimed to evaluate the potential occurrence of C. sumatrensis biotypes resistant to the herbicides chlorimuron-ethyl and glyphosate. Experiments were carried out under greenhouse conditions with four biotypes (Cascavel-2, Toledo-4, Tupãssi-6, and Assis Chateaubriand-7) possibly resistant to, as well as a population considered susceptible to chlorimuron-ethyl and glyphosate. To obtain dose-response curves, eight herbicide doses of chlorimuron-ethyl (0, 2.5, 5, 10, 20, 40, 80 and 160 g ha-1) and glyphosate (0, 90, 180, 360, 720, 1,440, 2,880 and 5,760 g e.a. ha-1) were applied and weed control and shoot biomass evaluations were made. Results provided evidence that two biotypes (Cascavel-2 and Tupãssi-6) were resistant to glyphosate and four biotypes (Cascavel-2, Toledo-4, Tupãssi-6 and Assis Chateaubriand-7) were resistant to chlorimuronethyl. Multiple resistance to glyphosate and chlorimuron was confirmed for biotypes Cascavel2 and Tupãssi 6. This is the first report on multiple resistance in Conyza sumatrensis, worldwide.